The Existence of Suluk During the Achmad Government in Rokan Hulu District (2006-2016) - Weni Diniari; Ahmal Ahmal; Asyrul Fikri (HISTORIA : Jurnal Program Studi Pendidikan Sejarah, 2022)
The purpose of this study is to determine: (1) To determine the condition of the existence of Suluk during the reign of Achmad in Rokan Hulu Regency, (2) To know the development of Suluk during the reign of Achmad in Rokan Hulu Regency, (3) To find out the impact of the existence of Suluk on people's lives during the reign of Achmad in Rokan Hulu Regency. This study uses a historical approach, data collection methods with field studies in the form of interviews and documentation as well as archive and library studies. This research was conducted in Rokan Hulu Regency. After the data is collected, the data examiner is carried out with source criticism, namely by testing the authenticity of the sources obtained by comparing one data with another, such as comparing the results of interviews with written evidence. Based on the results of this study, it can be concluded, namely, (1) The existence of Suluk during the Achmad period looks quite good with an increase in the number of Suluk congregations, (2) Suluk has developed quite rapidly, this is evidenced by the construction of quite a lot of Suluk Surau, (3) for the community. Suluk is very influential in everyday life in society.